Single-Dose Oral Amoxicillin or Linezolid for Prophylaxis of Experimental Endocarditis Due to Vancomycin-Susceptible and Vancomycin-Resistant Enterococcus faecalis - Moreillon, Philippe (American Society for Microbiology (ASM), 2007)
Endocarditis prophylaxis following genitourinary or gastrointestinal procedures targets Enterococcus faecalis. Prophylaxis recommendations advocate oral amoxicillin (2 g in the United States and 3 g in the United Kingdom) in moderate-risk patients and intravenous amoxicillin (2 g) or vancomycin (1 g) plus gentamicin in high-risk patients. While ampicillin-resistant (or amoxicillin-resistant) E. faecalis is still rare, there is a concern that these regimens might fail against vancomycin-resistant and/or aminoglycoside-resistant isolates. The present study tested oral linezolid as an alternative. Rats with catheter-induced aortic vegetations were given prophylaxis simulating human pharmacokinetics of oral amoxicillin (2- to 3-g single dose), oral linezolid (600 mg, single or multiple oral doses every 12 h), or intravenous vancomycin (1-g single dose). Rats were then inoculated with the minimum inoculum infecting 90% of the animals (90% infective dose [ID(90)]) or with 10 times the ID(90) of the vancomycin-susceptible E. faecalis strain JH2-2 or the vancomycin-resistant (VanA phenotype) E. faecalis strain UCN41. Amoxicillin was also tested with two additional vancomycin-susceptible E. faecalis strains, 309 and 1209. Animals were sacrificed 3 days later. All the tested bacteria were susceptible to amoxicillin and gentamicin. Single-dose amoxicillin provided 100% protection against all four isolates at both the ID(90) and 10 times the ID(90). In contrast, linezolid required up to four consecutive doses to provide full protection against the vancomycin-resistant isolate. Vancomycin protected only against the vancomycin-susceptible strain. The high efficacy of single-dose oral amoxicillin suggests that this regimen could be used for prophylaxis in both moderate-risk and high-risk patients without additional aminoglycosides. Linezolid appears to be less reliable, at least against the vancomycin-resistant strain.